Assessment of executive function in ADHD adolescents: contribution of performance tests and rating scales. Issue 8 (17th November 2018) - Krieger, Virginia; Amador-Campos, Juan Antonio
ABSTRACT: This study aimed to analyze performance on measures of neuropsychological and behavioral executive functions (EF) in adolescents with attention deficit hyperactivity disorder (ADHD), and to evaluate the utility of performance-based tests for predicting scores on behavioral EF ratings. One hundred eighteen adolescents (75 ADHD and 43 controls) aged 12–16 years performed neuropsychological tests and completed a behavior rating scale of EF. The ADHD group presented significantly lower scores than controls on Full Scale IQ (FSIQ) and all indexes of the WISC-IV, except the verbal comprehension index (VCI). The ADHD group had significantly lower scores on performance-based tests of working memory, planning and inhibition, and on EF rating scales. Scores on the cognitive EF working memory, planning and flexibility modestly predicted performance on behavioral EF. The results suggest that the combined use of performance-based tests and rating scales provides valuable complementary information that can improve the assessment of executive domains in ADHD.